Essays in Political Economy and International Public Finance - Kiss, Aron (Finanzwissenschaftliche Schriften, 2010)
The essays of the book are contributions to the game theoretic analysis of the State. Two of the essays develop further the analysis of political accountability. Political accountability is the study of how the behavior of politicians is shaped by the prospect of reelections. The essays in this book enrich this field by introducing aspects of coalition government and ideology. A third essay focuses on strategic behavior by states in repeated tax competition. The contribution of this essay is the reevaluation of a lower bound to admissible taxrates as a policy instrument to contain tax competition.